Analisis Waktu Tunggu Pelayanan Resep di Puskesmas Pasir Panjang Kota Kupang Bulan April Tahun 2018 - Ni Nyoman Yuliani; Victoria Letde (Badan Penelitian dan Pengembangan Daerah Kota Kupang, 2019)
One indicator of pharmacy services at the puskesmas is waiting time. The waiting time for drug service is the time period for the patient to submit the prescription until the patient receives the drug. This study aims to analyze the waiting time for prescription services at Pasir Panjang Health Center. This research is a non-experimental study with a descriptive design (survey research) on outpatients at Pasir Panjang Health Center and sampling using the purposive. Research time in April 2018. The results obtained were then analyzed for the suitability of the recipe for ready-made medicines and concoction drugs with minimum service standards and indicators of pharmaceutical services in the puskesmas in the long waiting time category. The number of recipes in this study were 353 recipes with details of 267 prescription drugs and 86 concoctions. The average waiting time for finished drugs is 11.38 minutes and the average waiting time for concoction is 13.45 minutes. This is in accordance with the indicators of pharmacy services at the puskesmas and the minimum service standards set by KEPMENKES No 129 / Menkes / SK / II / 2008 regarding prescription drug services that are ? 30 minutes, and pharmaceutical services for racic drugs which are ? 60 minutes.